حكم استخدام الذكاء الاصطناعي في التعليم والتعلم: برامج المحادثة الآلية نموذجا = Islamic ruling on using artificial intelligence in teaching and learning: AI chatbots as a case study - Md. Sawari, Mohd. Fuad; Mat Jubri@Shamsuddin, Mustafa (International Islamic University Malaysia, 2025)
This study aims to determine the Islamic ruling on using AI chatbots in education, particularly in Islamic studies. It examines the nature and characteristics of these programs and analyses their permissibility from a jurisprudential perspective through religious evidence, jurisprudential rules, and the objectives of Shariah. The study follows inductive and deductive approaches in surveying juristic opinions and deriving rulings from religious texts and jurisprudential principles. The study concludes that using AI chatbots in education is permissible with specific conditions, primarily: verifying information accuracy, comparing with recognized scholarly opinions, and considering them as assistive tools rather than the replacement of the teacher. The study also identifies six risk domains: information accuracy, teaching methodology, understanding and interpretation, educational aspects, identity and values, and practical implementation.